Analysis of the Accuracy of Ina-Cbg's Cost Based on the Type of Disease and Influencing Factors in the Inpatient Installation of RSUD dr. Soegiri Lamongan - Pujo Broto Iriawan Putra; Yuly Peristiowati; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
The result of monitoring and evaluation of Health Insurance Program (JKN) implementation especially in INA-CBG's claim process at Health Facility of Advanced Rujuan (FKRTL), there are differences of opinion for some cases between FKRTL and BPJS Kesehatan causing delay or problem in payment of claim INA-CBG's. The purpose of this study is to analyze the accuracy of INA-CBG's cost and the factors that influence in RSUD DR. Soegiri Lamongan. This research is a type of observational research with descriptive analytic research design with cross sectional research design according to hospital perspective. The sample in this study amounted to 393 respondents. Sampling technique Simple random sampling technique. The research instrument used using the expense bill file issued and the BPJS patient care claims file file with linear regression statistic test with α = 0.05. The cost component of the biggest Diabetes Mellitus disease is the median cost of Rp. 1.536.346. CVA disease average drug cost Rp. 1.135.399. The biggest DHF disease is the average room cost Rp. 814.067. Appendicitis medicines cost ± Rp. 1.633.961. The incremental cost of INA-CBG's and the actual cost of hospital in Diabetes Mellitus disease is Rp. 357.957, CVA disease difference of Rp. 2.151.170, DHF disease difference of Rp. 477,514 and in appendicitis disease the difference in average minus -Rp. 2,965,211. There is a difference (not appropriate) between the real cost and the cost of INA-CBG's in Diabetes Mellitus disease with p = 0,000. There is a difference (not appropriate) between the real cost and the cost of INA-CBG's on CVA disease with p value = 0.026. There is a similarity or precision between the real cost and the cost of INA-CBG's in DHF disease with a value of p = 0.159. There is a difference (not appropriate) between the real cost and the cost of INA-CBG's in Apendicitis disease with p = 0,000. There is a difference between the real cost and the cost of INA-CBG's in Diabetes mellitus, CVA, Apendicitis. Factors that affect the differences include room cost factors, drugs and medical action. For DHF disease there is no difference between the real cost and the cost of INA-CBG's.